Assessment of Leachate Pollution Potential of Unlined Landfill Using Leachate Pollution Index (LPI), Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2022)
Leachate produced from unlined landfills has become a global concern in recent times as a result of their interference with the environment. This is because of how complex leachate has become, given rise to serious pollution of nearby water resources. The effects of Leachate on the environment can be as a result of the toxicity of pollutants within the leachate which is largely tied to the waste generation patterns and climatic factors. This research work therefore, is to determine the leachate pollution index (LPI) at Yenagoa Central Waste Dump and its potential impact on nearby water resources during the first quarter of 2019 (March, 2019). Four different leachate samples were taken randomly from different locations of the dumpsite and mixed for homogeneity. Physico-chemical and microbial parameters were analyzed to identify the character of the leachate within the dumpsite during March, 2019 using standard laboratory methods. Parameters analyzed were, pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Hardness (TH), Ammonium (NH4+), Sulphate (SO42-), Nitrate (NO3-), Phosphate and Heavy Metals such as Cadmium (Cd), Chromium (Cr), Copper (Cu2+), Lead (Pb), Zinc (Zn), Calcium (Ca2+), Magnesium (Mg2+), Sodium (Na+), Iron (Fe2+) and Potassium (K+) ions, as well as Total coliform count. The leachate pollution index was computed to be 17.004 which was compared with the Indian standards for leachate disposal on Inland Waters (7.378). The results indicated that the leachate generated from the dumpsite was contaminated and therefore remediation measures should be put in place before it comes in contact with the environment.